1999
DOI: 10.1089/10430349950017635
|View full text |Cite
|
Sign up to set email alerts
|

Polylysine Modification of Adenoviral Fiber Protein Enhances Muscle Cell Transduction

Abstract: Adenoviral vectors (ADVs) are used widely for gene delivery to different tissues including muscle. One particularly promising use for ADVs is in the transfer of the dystrophin gene to the muscle of patients with Duchenne muscular dystrophy (DMD). However, studies in different animal models of DMD suggest that ADVs inefficiently transduce mature skeletal muscle. In this article we test whether AdZ.F(pK7), a genetically modified ADV that expresses a polylysine moiety on the end of the fiber protein, could enhanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
50
0
1

Year Published

1999
1999
2007
2007

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 79 publications
(53 citation statements)
references
References 22 publications
2
50
0
1
Order By: Relevance
“…Expanded and efficient gene transfer has been reported based on the use of mutant fiber proteins containing a stretch of lysine residues (23)(24)(25). However, there has been no report on the difference in gene transfer activity and toxicity in vivo between the conventional Ad vector and the fibermodified Ad vector containing the K7 peptide.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Expanded and efficient gene transfer has been reported based on the use of mutant fiber proteins containing a stretch of lysine residues (23)(24)(25). However, there has been no report on the difference in gene transfer activity and toxicity in vivo between the conventional Ad vector and the fibermodified Ad vector containing the K7 peptide.…”
Section: Discussionmentioning
confidence: 99%
“…We found that the fiber-modified Ad vector containing a stretch of lysine residues (K7 (KKKKKKK) peptide) (23)(24)(25) that target heparan sulfates on the cellular surface greatly reduced IL-6 and liver toxicity after i.v. injection into mice compared with the conventional Ad vector.…”
Section: Fiber-modified Adenovirus Vectors Decrease Livermentioning
confidence: 99%
“…bgal activity and protein concentration were measured as described previously. 11,22 Concurrently measured background bgal activity levels in uninjected muscle extracts are subtracted from all sample values.…”
Section: B-galactosidase Expression Studies By Onpg and X-gal Stainingmentioning
confidence: 99%
“…The selected ligand is a peptide composed of seven lysine residues (7K) which is known to confer to the modified virus the ability to efficiently bind heparan sulfate-containing glycoproteins on the surface of target cells. [27][28][29][30] The growth characteristics of viruses carrying or not carrying the additional ligand have been compared using heparan sulfate-containing 293 cells (Figure 5a). We thus demonstrated that the Ad/Fb-Ser408Glu-7K virus propagates as efficiently as the wild-type virus on 293 cells while the kinetic growth of the Ad-LacZ/Fb-Ser408Glu was significantly reduced (Figure 5a).…”
Section: Incorporation Of An Alternative Ligandmentioning
confidence: 99%